DeFi - Kim, Seoyoung (--For dummies., 2023)
The promise of decentralized finance (DeFi) as a disruptor to financial institutions makes it must-know for anyone involved in finance. DeFi For Dummies provides an easy-to-understand option for unraveling the past, present, and future of DeFi. Understand current DeFi applications, including how to build basic applications on the leading platforms, and get a look into the future's most promising new DeFi solutions. Staying ahead of the game is critical for finance professionals these days, and this Dummies guide makes it possible, with full coverage of how DeFi affects asset management, lending and borrowing, and investment markets. Wrap your mind around DeFi and start getting hands on, the Dummies way. - Learn how the DeFi revolution started and where it's going - Get insight into opportunities for getting started and building value with DeFi - Discover the leading assets, exchanges, and marketplaces built on DeFi principles - Create secure DeFi applications on established platforms This book is great for current pros or active investors in the world of finance who need to get up to speed on the world of DeFi as quickly and clearly as possible.